Nursing education in future perspective - Jose, P (Journal of Universal College of Medical Sciences, 2014)
Trends in health care suggest changes in nursing practice and implications for nursing education. Changing demographics, emphasis on health promotion, health care costs, movement toward community-based care, and expanding technology are factors that shape the health care system of the future and educational preparation of nurses. Faculties are faced with preparing students for future practice that will be more complex and specialized than it is now; will be provided in multiple settings; and will require extensive knowledge, critical thinking and other cognitive skills, technologic and psychomotor skills, and a value system for making ethical decisions. Outcomes of nursing education program include learning to learn, handling ambiguity, thinking like a professional, and accepting responsibility for decisions made in practice. For nursing to assume a central role in the health care system of tomorrow, reform in nursing education is needed today. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10492 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 41-44